Fluorescent BAPAD Dendrimeric Antigens Are Efficiently Internalized by Human Dendritic Cells - Mesa-Antunez, Pablo (Polymers (Basel), 2016)
A new fluorescent dendrimeric antigen (DeAn) based on a dendron with amoxicilloyl terminal groups was synthesized. The synthesis was carried out using a novel class of all-aliphatic polyamide dendrimer (BisAminoalkylPolyAmide Dendrimers, or BAPAD) involving the direct condensation of 3,3′-diazidopivalic acid as a building block. Iterative azide reduction/amide formation increases the dendrimer generation. The BAPAD dendrimer was designed with a cystamine core. Reduction of the disulfide bond allows the incorporation of BAPAD dendrons into a 1,8-naphthalimide functionalized with a maleimide group. The fluorescence properties of DeAn were studied in PBS and compared with the properties of an equivalent dendron possessing amino-terminal groups. Both molecules shown high fluorescence quantum yields in PBS and could readily be visualized by fluorescence microscopy. DeAn was used as a synthetic antigen in a biomedical assay that tests their potential as an amoxicillin carrier in drug internalization by dendritic cells (DC) from tolerant and allergic patients. Cytometry data suggest that the dendrons are non-toxic and easily internalized by DCs, while confocal microscopy images indicate that the compounds are preferentially accumulated in the cytoplasm. These results indicate that BAPAD dendrons are good candidates for synthetic scaffolds for biomedical applications.